GUARANTEES FOR IMPLEMENTATION OF THE INSTITUTE OF THE BASIS OF THE CONSTITUTIONAL ORDER: CONCEPT, PURPOSE, TYPES, REALITY (Journal of actual problems of jurisprudence, 2019)
In this article the problems of implementation's guarantee of institution of constitutional regime's bases in Kazakhstan areconsidered.